Pharmacovigilance in children in Camagüey Province, Cuba - Bárzaga Arencibia, Z.; López Leyva, A.; Mejías Peña, Y.; González Reyes, A.R.; Fernández Manzano, E.; Choonara, Imti (Springer Verlag (Germany), 2012)
Purpose: Our aim was to describe the adverse drug reactions (ADRs) detected following increased education about pharmacovigilance and drug toxicity in children in Camagüey Province, Cuba. Methods: Over a period of 24 months (January 2009 to December 2010), all reports of suspected ADRs in children to the Provincial Pharmacovigilance Centre in Camagüey Province were analysed. ADRs were classified in relation to causality and severity. Results: There were 533 reports involving suspected ADRs in children in the period. Almost one third of the reports received were classified as moderate (155, 29%) or severe (10, 2%). There was one fatality in association with the use of ceftriaxone. Vaccines and antibiotics were responsible for most of the ADR reports (392, 74%) and for all ten severe ADRs. After an intensive educational package, both within the community and the Children’s Hospital, the number of reports increased from 124 in 2008 to 161 in 2009 and 372 in 2010. This was equivalent to a reporting rate of 879 and 2,031 reports per million children per year for 2009 and 2010, respectively. Conclusions: The incidence of ADRs in children Camagüey Province, Cuba, is greater than previously reported. An educational intervention about pharmacovigilance and drug toxicity in children can improve the reporting of ADRs.